Integration of Immigrants and the Theory of Recognition 'Just Integration' - Goksel, Gulay Ugur (International Political Theory,, 2018)
This book approaches the issue of immigrant integration as a democratic justice problem. Based on Honneth's recognition theory, it introduces the concept of 'Just Integration', which challenges the capacity of the actual recognition order of the host society to include its immigrants as full members. The study criticizes the current political obsession to restore the social cohesion of the host society in the face of immigration. It argues that this perception inhibits host societies from recognizing their immigrants as individuals who have authentic skills, qualifications and identities in addition to their ethnic, cultural and religious attachments. The author applies the concept of 'Just Integration' to the real pathologies that immigrants/refugees suffer in Canada and Turkey, providing guidelines for progress towards better integration of immigrants within host societies and institutions. .